Ο ΕΛΛΗΝΙΚΟΣ ΕΜΦΥΛΙΟΣ ΠΟΛΕΜΟΣ ΚΑΙ Ο ΙΣΠΑΝΙΚΟΣ ΤΥΠΟΣ ΤΟΥ ΦΡΑΝΚΙΣΜΟΥ - ΜΕΛΛΑ, ΖΩΗ (Μνήμων, 2005)
Zoi Mella, The Greek Civil War and the Spanish Press during Franco's Dictatorship In this article we would like to approach a quite unknown subject: the presence of the Greek Civil War in the Spanish Press. Our objective was to ascertain the impact this event had at the post war Spanish Press. How would react Spain in view of such a confrontation, especially since it had already experimented a Civil War? It was a complicated period for Greece, as well as for Spain, a time when both countries experienced problems of different nature but equally serious: Greece was suffering the devastating consequences of the Second World War and Spain was trying to encounter the contempt of the international political world. The Greek Civil War was the first confrontation between two worlds that were exiting reinforced from the Second World War. It became the field of conflict between the USSR and the Anglo-Saxon allies during several years. The interior problem of some rebels, who couldn't, or wouldn't, adapt themselves to the new post war situation or were discontented with the new regime, was transformed to an international matter of great impact, that managed to confront USSR, on one hand, and the US and Great Britain, on the other, in the International Organism of the United Nations. Our interest was centred in the various approaches that the newspapers and the magazines of the time made. Moreover we were interested in the points of view and the conclusions manifested by the diverse papers, according to their political and ideological affinities, without forgetting the strict regime of control and censure that was in force at that moment. This investigation forms part of a broader subject that is the bilateral relations of these two countries, rather different at first sight, that during the XX century were affected by very similar events, such as a civil war.